The Impact of Implementing Restorative Justice on Children in Conflict with the Law in Street Crimes - Sulidewi, Nuraisyah; Prasetyoningsih, Nanik (Faculty of Law, Universitas Pekalongan, 2024)
Cases of children in conflict with the Law, especially in criminal cases involving street crimes, still pose a threat to community members. The forms of threats and crimes include carrying sharp weapons to harm other people, mugging, beatings, beatings, and even stabbings carried out with a certain motive or without a motive (random). By the child protection law and the juvenile justice system in force in Indonesia, children caught in criminal acts will receive special treatment. Namely, efforts will be made so that children in conflict with the Law can be fairly restored to their original condition for both the victim and the perpetrator. Still, their nature is not retaliation, so efforts are made to resolve criminal cases outside of court or what is known as a restorative justice approach. This normative research uses the statutory, conceptual, and case approaches. The type of data used is secondary data sources obtained through literature study and document study, as well as from secondary and primary legal materials. The results of this research show that implementing a restorative justice approach in resolving criminal cases for children in conflict with the Law, it is hoped that will have a positive impact, namely developing children according to their age so that legal awareness will grow and they will not repeat similar crimes. Then, resolving criminal cases outside of court will prevent children from interacting with inmates in prison and prevent children from being labelled as criminals because children still have a long future.